Unified magnetomechanical homogenization framework with application to magnetorheological elastomers - Chatzigeorgiou, Georgios; Javili, Ali; Steinmann, Paul (Mathematics and Mechanics of Solids, 2012)
The aim of this work is to present a general homogenization framework with application to magnetorheological elastomers under large deformation processes. The macroscale and microscale magnetomechanical responses of the composite in the material and spatial description are presented and the conditions for a well-established homogenization problem in Lagrangian description are identified. The connection between the macroscopic magnetomechanical field variables and the volume averaging of the corresponding microscopic variables in the Eulerian description is examined for several types of boundary conditions. It is shown that the use of kinematic and magnetic field potentials instead of kinetic field and magnetic induction potentials provides a more appropriate homogenization process.
UnivIS-Import:2015-04-14:Pub.2012.tech.FT.FT-TM.unifie